2022
DOI: 10.4103/iju.iju_331_21
|View full text |Cite
|
Sign up to set email alerts
|

Thulium fiber laser versus holmium

Abstract: Introduction: We aimed to evaluate the effectiveness and safety of the newly launched thulium fiber laser (TFL) with holmium laser lithotripsy in the miniaturized percutaneous nephrolithotomy (Miniperc) procedure for renal stones. Methods: The prospective study included patients with renal stones of size >1 cm to ≤3 cm. The patients who opted for extracorporeal shock wave lithotripsy, retrograde intrarenal surgeries, and stones >3 cm were excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Majdalany et al assessed e ciency measures for Ho: YAG with Moses technology and found that for a mean stone volume of 290 mm3, mean laser e cacy was 38.2 J/mm3 and the mean ablation speed was 0.9 mm3/s [24]. In a RCT comparing Ho: YAG and TFL during mini-PCNL, the authors noted shorter stone fragmentation time and shorter operative time in favour of TFL [25].…”
Section: Discussionmentioning
confidence: 99%
“…Majdalany et al assessed e ciency measures for Ho: YAG with Moses technology and found that for a mean stone volume of 290 mm3, mean laser e cacy was 38.2 J/mm3 and the mean ablation speed was 0.9 mm3/s [24]. In a RCT comparing Ho: YAG and TFL during mini-PCNL, the authors noted shorter stone fragmentation time and shorter operative time in favour of TFL [25].…”
Section: Discussionmentioning
confidence: 99%
“…Die neuesten Fortschritte in der Miniaturisierung der PCNL ermöglichen wesentlich kleinere Zugänge, wodurch Transfusionsraten, postoperative Schmerzen und Krankenhausaufenthalte verringert werden, während die Steinfreiheitsraten im Vergleich zu der Standard-PCNL aufrechterhalten werden [38]. Da der TFL vielversprechende Ergebnisse bei der URS gezeigt hat, haben einige Arbeitsgruppen seine Wirksamkeit auch bei der Mini-PCNL evaluiert [39,40,41].…”
Section: Perkutane Nephrolitholapaxieunclassified
“…Ein kürzlich veröffentlichter Vergleich zwischen dem TFL und dem Ho:YAG-Laser mit ähnlichen Fragmentierungseinstellungen bei Patienten, die eine Mini-PCNL (16,5-17,5 Fr) erhielten, zeigte kürzere Desintegrationszeiten und eine geringere Operationszeit in der TFL-Gruppe (11 Minuten 19 Sekunden vs. 20 Minuten 45 Sekunden, p<0,001; und 55 Minuten vs. 68 Minuten, p = 0,001). In dieser Serie erwies sich der TFL während der PCNL als sicher, obwohl die Patienten im Vergleich zur Ho:YAG-Laser-Gruppe eine leicht verlängerte Hämaturie aufwiesen [41]. In einer Studie, die diese Modalitäten verglich, war bei der URS eine schlechte Sicht mit höheren Frequenzen korreliert, was jedoch nicht bei der PCNL bestätigt werden konnte [42].…”
Section: Perkutane Nephrolitholapaxieunclassified
“…with the current development of thulium fibre laser (TFL), the incidence of self-limiting haematuria is higher [17]. Cakiroglu et al [18 & ] also evaluated the efficacy of RIRS and Ho:YAG lithotripsy in the treatment of 30 symptomatic calyceal diverticulum stones.…”
Section: Key Pointsmentioning
confidence: 99%